Burden of hereditary cancer susceptibility in unselected patients with pancreatic ductal adenocarcinoma referred for germline screening. (7th April 2020) - Cremin, Carol; Lee, Michael Kuan‐Ching; Hong, Quan; Hoeschen, Carolyn; Mackenzie, Anna; Dixon, Katherine; McCullum, Mary; Nuk, Jennifer; Kalloger, Steve; Karasinska, Joanna; Scudamore, Charles; Kim, Peter T. W.; et al.
Abstract: Background: Recent guidelines recommend consideration of germline testing for all newly diagnosed pancreatic ductal adenocarcinoma (PDAC). The primary aim of this study was to determine the burden of hereditary cancer susceptibility in PDAC. A secondary aim was to compare genetic testing uptake rates across different modes of genetic counselling. Patients and Methods: All patients diagnosed with PDAC in the province of British Columbia, Canada referred to a population‐based hereditary cancer program were eligible for multi‐gene panel testing, irrespective of cancer family history. Any healthcare provider or patients themselves could refer. Results: A total of 305 patients with PDAC were referred between July 2016 and January 2019. Two hundred thirty‐five patients attended a consultation and 177 completed index germline genetic testing. 25/177 (14.1%) of unrelated patients had a pathogenic variant (PV); 19/25 PV were in known PDAC susceptibility genes with cancer screening or risk‐reduction implications. PDAC was significantly associated with PV in ATM (OR, 7.73; 95% CI, 3.10 to 19.33, P = 6.14E‐05) when comparing age and gender and ethnicity‐matched controls tested on the same platform. The overall uptake rate for index testing was 59.2% and was significantly higher with 1‐on‐1 consultations and group consultations compared to telehealth consultations (88.9% vs 82.9% vs 61.8%, P < .001). Conclusion: In a prospective clinic‐based cohort of patients with PDAC referred for testing irrespective of family history, germline PV were detected in 14.1%. PV in ATM accounted for half of all PVs and were significantly associated with PDAC. These findings support recent guidelines and will guide future service planning in this population. Abstract : In a prospective clinic‐based cohort of patients with PDAC referred for testing irrespective of family history, germline PV were detected in 14.1%. PV in ATM accounted for half of all PVs and were significantly associated with PDAC. These findings support recent guidelines and will guide future service planning in this population.